Vertical stratification influences global patterns of biodiversity. Issue 2 (16th August 2018) - Oliveira, Brunno F.; Scheffers, Brett R.
Abstract : Species distributions in terrestrial ecosystems are three‐dimensional, spanning both the horizontal landscape and the vertical space provided by the physical environment. Classical hypotheses suggest that communities become more vertically stratified with increasing species richness, owing to reduced competition or finer niche subdivision. However, this assertion remains untested in the context of the broader realm of biogeography. Here, integrating traits and distribution data for amphibians globally, we show how vertical strategies interact with the physical and climatic environments to govern global patterns of species richness and community composition. Our results reveal a marked latitudinal shift in strategies of vertical habitat use, from highly arboreal assemblages in the tropics to highly fossorial assemblages in sub‐tropical and temperate regions. Arboreality is strongly associated with precipitation, vegetation structure and climatic stability, whereas fossoriality is more common in dry environments with high diurnal temperature range and low vegetation structure. These analyses shed light on the importance of vertical stratification for species coexistence in species‐rich regions. As certain tropical habitats become drier from climate change, the rich biological diversity that is emblematic of the tropics may transition from vertically stratified to 'flattened', with future communities living mostly on or beneath the ground.